2017
DOI: 10.1016/j.joms.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Is Hyaluronic Acid or Corticosteroid Superior to Lactated Ringer Solution in the Short-Term Reduction of Temporomandibular Joint Pain After Arthrocentesis? Part 1

Abstract: Arthrocentesis alone is as efficacious as arthrocentesis with HA or CS in decreasing TMJ pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 65 publications
0
33
0
9
Order By: Relevance
“…The use of HA (as reported in 3 trials of this review) after arthrocentesis is controversial at best, with low quality of literature . Some support the use of HA claiming its lubricating effect provides faster and longer relief from pain, while another study reports no significant difference in outcome while using arthrocentesis alone . Similarly, the role of splint after arthrocentesis is questionable.…”
Section: Discussionmentioning
confidence: 93%
“…The use of HA (as reported in 3 trials of this review) after arthrocentesis is controversial at best, with low quality of literature . Some support the use of HA claiming its lubricating effect provides faster and longer relief from pain, while another study reports no significant difference in outcome while using arthrocentesis alone . Similarly, the role of splint after arthrocentesis is questionable.…”
Section: Discussionmentioning
confidence: 93%
“…The question becomes whether TMJ arthralgia is caused by an inflammation triggered by IA agents, which is diluted at the IA intervention, or whether the nerve block anaesthetic stops a windup phenomenon. In addition, in arthrocentesis studies in which the intervention procedure was completed with or without deposition of corticosteroids for treatment of TMJ arthralgia, arthrosis and internal derangement have no significant effects on pain intensity . Thus, it seems obvious that the combination of procedures, local anaesthetic and injected fluid reduce TMJ pain.…”
Section: Discussionmentioning
confidence: 99%
“…The initial literature search yielded on 2067 articles (Cochrane Library=45/ Web of Science=5/ Google Scholar=1390/ PubMed=47/ ProQuest=107/ Scopus=473), in which 1402 articles remained after removing duplicates. After the first screening based on the title and abstract, 11 studies ( 13 , 16 , 17 , 20 - 27 ) were found eligible which reached to 7 studies ( 13 , 17 , 20 - 24 ) after excluding high risk articles (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%